O Bolo e Borra de Café: análise da representação da identidade cultural na Paraíba - Sousa, Rebeca Oliveira (2014)
This paper aims to examine two local productions short, film showing, how narrative core a father and daughter, and depicting the Paraíba in different historical times: "O Bolo" and "Borra de Café". Owing to the growing film market and audiovisual revealed through the emergence of numerous festivals, and also the improvement of techniques, equipment cheapening promoting greater democratization of this cultural asset, we have confronted increasingly with local productions that despite globalization and the evolution of media, common features related to cultural identity in the region where they were produced: the Paraíba. Through the study of forms and contents covering scenographic elements, narrative, sound, among others, will try to understand what the motivation of the use in creative processes, and where it is possible to identify, by means of analogies and symbols, cultural identity paraibana elected in the movies produced in the local context.